THE USE OF KAHOOT AS THE ALTERNATIVE ASSIGNMENT IN ONLINE LEARNING DURING PANDEMIC AT SMP MUHAMMADIYAH 61 MEDAN: TEACHERS PERSPECTIVES - Yayuk Hayulina Manurung; Fatimah Sari Siregar (Proceeding International Seminar of Islamic Studies, 2022)
This study was aimed to describe the teachers perspective on the use of kahoot as the alternative assignment during pandemic at SMP Muhammadiyah 61 Medan. The qualitative method was applied in this research. The result showed that the teachers perspective on the use of kahoot as the alternative assignment in online learning was very good. However it is important for the improvement of how to use the technology for teaching-learning activities and especially in online assignment because the teacher can learn how to use Kahoot! properly by avoiding the disadvantages found in this research. The research raises important questions about how to handle the constraints encountered by the teacher while using Kahoot! It is very crucial to provide users with adequate technical support.Keywords: Kahoot, Teachers, Perspective, Online, Assignment